Analysis of PAEs in semen of infertile men. (January 2015) - Wang, Sheng-Yuan; Wang, Yu; Xie, Fang-Qin; Li, Yan-Xing; Wan, Xue-Lian; Ma, Wei-Wei; Wang, De-Cai; Wu, Yong-Hui
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: Phthalates are environmental chemicals with reproductive toxicity and estrogenic effects in animals. They are of increasing concern to human health. Aim: To determine whether phthalate levels in semen were associated with infertility. Methods: Using semen samples from 107 infertile and 94 fertile men, the presence and quantity of five phthalate esters were measured using high-performance liquid chromatography (HPLC). Using data collected from questionnaires and clinical examinations, the correlation between phthalate exposure and semen quality was analyzed. Results: The cumulative levels of the measured phthalate esters were significantly higher in the infertility group compared to the control group (P<0·05). Concentrations of the five phthalate esters in men varied by age with older men showing higher cumulative levels. Conclusions: The presence of phthalates may contribute to male infertility in our study population.